Intentional mindwandering and unintentional mindwandering are differentially associated with the experience of self-alienation. (February 2022) - Vess, Matthew; Maffly-Kipp, Joseph
Abstract: Self-alienation is a component of authenticity robustly connected to psychological flourishing. Building on theorizing about the importance of an experiential sense of self-ownership for feeling connected to one's true self, we tested whether intentional and unintentional mindwandering differentially correlate with the experience of self-alienation. Participants ( N  = 278) completed a baseline measure of trait self-alienation, followed by 6 weekly assessments of self-alienation and mindwandering. Weekly fluctuations in intentional mindwandering were negatively associated with self-alienation and weekly fluctuations in unintentional mindwandering were positively associated with self-alienation. These findings advance what is known about the link between self-alienation and mindwandering, and provide evidence for the importance of volition for self-alienation.